Conservative Treatment of Stage IA1 Cervical Carcinoma Without Lymphovascular Space Invasion: A 20-year Retrospective Study in Brazil - Alberton, Daniele Lima; Salcedo, Mila Pontremoli; Zen, Raquel Potrich; Ferreira, Charles Francisco; Schmeler, Kathleen; Pessini, Suzana Arenhart (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Purpose: To evaluate recurrence rates and risk factors among women with stage IA1 cervical cancer without lymph vascular space invasion managed conservatively.Methods: retrospective review of women with stage IA1 squamous cervical cancer who underwent cold knife cone or loop electrosurgical excision procedure, between 1994 and 2015, at a gynecologic oncology center in Southern Brazil. Age at diagnosis, pre-conization findings, conization method, margin status, residual disease, recurrence and survival rates were collected and analyzed.Results: 26 women diagnosed with stage IA1 squamous cervical cancer without lymphovascular space invasion underwent conservative management and had at least 12 months follow-up. The mean follow-up was 44.6 months. The mean age at diagnosis was 40.9 years. Median first intercourse occurred at age 16 years, 11.5% were nulliparous and 30.8% were current or past tobacco smokers. There was one Human immunodeficiency virus positive patient diagnosed with cervical intraepithelial neoplasia grade 2 at 30 months after surgery. However, there were no patients diagnosed with recurrent invasive cervical cancer and there were no deaths due to cervical cancer or other causes in the cohort.Conclusion: Excellent outcomes were noted in women with stage IA1 cervical cancer without lymphovascular space invasion and with negative margins who were managed conservatively, even in a developing country.
Keywords: Uterine cervical neoplasms; Conization; Conservative treatment; Recurrence; Squamous cell carcinoma